2002
DOI: 10.1111/j.1547-5069.2002.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Distress and Prenatal Attachment in Pregnancy After Perinatal Loss

Abstract: These findings do not support the theory that depressive symptoms and pregnancy-specific anxiety affect subsequent parent-infant attachment in a pregnancy after perinatal loss. However, they do provide insight into the continuing influence of parents' previous loss experience on their depressive symptoms and pregnancy-specific anxiety in subsequent pregnancies. Families should be assessed to examine the potential long-term influence of emotional distress as a result of prior perinatal loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
119
4
14

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(145 citation statements)
references
References 27 publications
8
119
4
14
Order By: Relevance
“…Seeing an image of the fetus made the pregnancy more 'real' , and hence it became difficult to remain emotionally detached. 34 Interestingly, in 'normal' circumstances, maternal attachment has been shown to increase significantly across time 32,35,36 with highest overall levels of attachment in the second trimester. 37 NIPD is therefore likely to be valuable for those receiving news in the first trimester that the fetus is of the unaffected sex as they are able to emotionally invest in their pregnancy before the time when the bonding process naturally peaks.…”
Section: Discussionmentioning
confidence: 99%
“…Seeing an image of the fetus made the pregnancy more 'real' , and hence it became difficult to remain emotionally detached. 34 Interestingly, in 'normal' circumstances, maternal attachment has been shown to increase significantly across time 32,35,36 with highest overall levels of attachment in the second trimester. 37 NIPD is therefore likely to be valuable for those receiving news in the first trimester that the fetus is of the unaffected sex as they are able to emotionally invest in their pregnancy before the time when the bonding process naturally peaks.…”
Section: Discussionmentioning
confidence: 99%
“…Grieving of parents, who had experienced loss of a baby but did not have the opportunity to know their baby, was different from other types of grieving (de Montigny et al, 1999). Armstrong (2001;2002;2007) showed that parents with previous losses had significantly higher antenatal anxiety on the outcome of the current pregnancy than the expectant parents with no history of perinatal loss. Couples who experienced the death of a baby were significantly more likely to have one or both partners distressed, compared to non-bereaved couples (Armstrong and Hutti, 1998;de Montigny et al, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…4 Various studies have described high rates of symptoms of anxiety and depression following perinatal loss. 1,5,6 Nevertheless, little is known of the consequences of continuous grief on future pregnancies. 1 Few studies have evaluated quality of life during pregnancy.…”
Section: Introductionmentioning
confidence: 99%